Disposition of a single oral dose of a cannabidiol medication in healthy cats - Jukier, Tom; Cruz-Espindola, Crisanta; Martin, Doug; Boothe, Dawn M. (Frontiers in Veterinary Science, 2023)
The historical use of the marijuana plant for medicinal purposes is long. Recently, the Food and Drug Administration has approved a highly purified cannabidiol medication for the add on therapy in people with certain forms of epilepsy. With the increase in interest of the use of cannabidiol in the veterinary community, the aim of this study was to describe the disposition of a single dose of a cannabidiol medication in healthy cats in both the fed and fasted state. Pharmacokinetic analysis reveals that relative bioavailability of cannabidiol shows a nearly three-fold improvement when administered in the fed state compared to the fasted state. Additionally, concentrations achieved at a dose of 5mg/kg, may be sufficient to explore the therapeutic potential in cats with epilepsy.